Demographic and Systematic Factors Affecting Student Voter Turnout: An Empirical Study For Africa’s Largest Distance Higher Education Institution (Journal of Student Affairs in Africa, 2022)
Public HEI’s in South Africa conducts the Student Representative Council elections yearly, however, there is a paucity of studies to determine factors that affect voter turnout.  This descriptive quantitative study conducted an empirical analysis of factors influencing student’s voter participation at Africa’s largest Open Distance eLearning (ODeL) institution. An electronic survey instrument was distributed amongst the sampled students and yielded a final response count of 6 851.  A joint descriptive statistical analyses and a binary logistic regression model were applied to analyse data. Regression analysis revealed that there was a significant relationship between students having encountered one or more of marketing initiatives employed in the election project and voter participation. This positions marketing as a significant predictor of student voting given that respondents who encountered the SRC election marketing initiatives were seven times more likely to vote, as shown by the Odds Ratio of [OR=7.9 (95% CI:6.6-9.3), p=0.001].  The second-highest predictor of voting in this study was the closing date impact; students respondents who indicated that the voting period was long enough were two times more likely to vote compared to those who did not believe it was long enough [OR=2.2 (95% CI: 1.9-2.7), p-value